Evaluation of Two Ergonomic Intervention Programs in Reducing Ergonomic Risk Factors Contributing to Musculoskeletal Pain Among School Children - Ismail, Syazwan Aizat (2010)
Introduction: An intervention study was carried out from February 2009 until August 2009 with the objective of investigating the cost effectiveness of two ergonomics intervention programs in reducing ergonomics risk factors among 229 school children in 2nd Grade (age 8 years) and 5th Grade (age 11 years) from three schools. Methodology: An intervention study design was carried out, in which for group 1 ergonomically designed furniture were used in the intervention program together with instructions on the proper usage. Group 2 implemented an ergonomics program with intensive health promotion consisting of exercises, educational materials and lectures to reduce ergonomics risk. Musculoskeletal symptoms were recorded using Standardized Nordic Body Map Questionnaires. In measuring the risk factors of each intervention program, Rapid Upper Limb Assessment (RULA) was used to assess the risk from awkward posture perform while seating. Ergonomics awareness test (EAT) was performed in evaluating the awareness level of ergonomics risks existed in the school environment. Tanita weight measure the school bag weight of each respondent. Results: A significant (p<0.05) reduction of RULA score were observed among those in Group 1 and Group 2 (2nd and 5th grader) with no significant changes of risk among those in the group. School bag weight was significantly reduced from baseline to post intervention assessment among 2nd grader in group 1. Although there is a trend of school bag weight reduction from baseline to post intervention program, no significant reduction of school bag weight reduction of school bag weight observed among 5th grader of group 1 and 2. The ergonomics awareness test shows an increasing trend for both groups while control group shows that Group 1 in more effective than Group 2 in reducing the risk from school bag weight and improving the knowledge in ergonomics awareness while Group 2 effectively manage in reducing postural risk. Conclusions: By using ergonomics furniture with proper instructions, the study revealed that the risk from the heavy school bag weight was reduced and ergonomics knowledge among the students increases. Health promotion program manage to reduce postural risk among those using current furniture. Keywords: Schoolchildren, musculoskeletal pain, rapid upper limb assessment, ergonomics intervention programs, bag weight, and ergonomics awareness test.